Recovery Strategies of Tourism Businesses in COVID-19 Pandemic in Indonesia - Juhanda; Fulka 'Ilmy Avicenna Ralinas; Faozen; Hadi Jatmiko (Research and Community Service Center, Politeknik Pariwisata NHI Bandung, 2022)
This paper explores compatible recovery strategies executed by the tourism business doers to survive their businesses due to the undeniable stagnation of the Covid-19 pandemic in Indonesia. The present study utilizes semi-structured online interviews to explore participants' activities, experiences, and strategies to maintain the tourism business during the COVID-19 pandemic. We garnered all data concerning the practical field experiences of participants by distributing google forms and collected further information from communication via telephone and WhatsApp chats. The research results showcased three strategies for the tourism business survival: improving hygiene and health standards, intensifying promotion, and operational cost control. Practically, this research will benefit tourism businesses to be more resilient in uncertain conditions in the future. The current study also contributes to the authority to resolve relevant policies incorporated with economic recovery related to the crisis due to the pandemic.